Teologi Feminisme Riffat Hasan dan Rekonstruksi Pemahaman Atas Kedudukan dan Peran Wanita - M. Mukhtasar Syamsuddin; Arqom Kuswanjono (Jurnal Filsafat "WISDOM", 1999)
This research is purposed as an effort to gain a new understanding about status and role of women according to Riffat Hasan's thought. The probelms are; what is status and role of women likes in Riffat Hasan's feminism theology and how did feminism theology reconstruct the comprehension on status and role of women? The elements of the philosophical method that are used in this research are; interpretation, internal coherence, heuristic, and description.Riffat Hasan had analyzed critically the root of the status and role women probelm by disclosing the influence of patriach traditions in the view and religion teachings interpretations that are always used as legitimatization for man's superiority. Considering the Al Qur"an, Riffat Hassan formulated a comprehension that essentially, the status and role of women is equal. Both men and women are created from nafs (living entity) the one is not have superiority on the other one.